Modeling Credit Aggregates - Sylvia Kaufmann; Maria Teresa Valderrama (Oesterreichische Nationalbank (OeNB), 2004)
The purpose of this paper is to model both loans to households and to non-financial corporations as well as their relation to interest rates and demand variables for Austria, Germany, the Netherlands and the United Kingdom. Credit aggregates are modeled using a Markov-switching vector autoregressive model, which allows testing as to whether shocks to the economy have stronger effects during tight credit regimes or economic downturns. The analysis of the above-mentioned countries makes it possible to assess the differences in the amplifying and asymmetric effects of credit aggregates between marketbased and bank-based financial systems.
Keywords: C32; E44; E51; 330; Asymmetry and amplification; credit aggregates; market-based and bank-based financial systems